Pore-Throat Structure and Fractal Characteristics of Tight Sandstones: A Case Study from the Chang 63 Sublayer, Southeast Ordos Basin. (20th March 2023) - Han, Zhuo; Zhou, Yanan; Wei, Fanrong; Zhang, Qian; Fan, Pingtian; Deng, Chao; Gong, Jiantao; Cheng, Xin; Ma, Erping; Wu, Hanning
Abstract : The micropore-throat structure is a controlling factor on the capacity of storage and seepage for the tight sandstone reservoirs. Therefore, quantitatively analyzing the pore-throat structure is crucial for realizing the oil accumulated in the tight reservoirs. To study the micropore-throat, a battery of experiments such as casting thin sections, scanning electron microscopy, high-pressure mercury injection, and the petrophysical characteristics of reservoirs were conducted on ten samples gathered in the Late Triassic Chang 63 sublayer in the Southeast Ordos Basin, China. The main pore types of the samples are intergranular pores, feldspar dissolved pores, and intergranular dissolved pores. Meanwhile, the pore-throat structure of each sample was identified as large pores, medium pores, and small pores by combining the result of HPMI with fractal theory. The corresponding mean values of the fractal dimension D for large, medium, and small pores are 2.83, 2.69, and 2.31, respectively, indicating that the complex structure and strong heterogeneity were presented in the large pores according to the maximum fractal dimension. In addition, the fractal dimension of the medium pores (D P − 2 ) has a negative correlation with porosity, permeability, median pore-throat radius, maximum mercury saturation, mercury withdrawal efficiency, displacement pressure, and content of quartz, while a positive correlation with feldspar content, sorting coefficient, and coefficient of variation. Thus, the reservoir space and seepage capacity of all samples in this study were determined by the size, complexity, and distribution of the medium pores. Furthermore, the content of quartz contributes to the storage of the reservoir and the homogeneity of the pore-throat structure, thereby the storage capacity improves with the increase of quartz content. Feldspar dissolution pores are developed widely in the study area, leading to various pores with diverse types, sizes, complex structures, and large fractal dimensions. Although the storage capacity of tight sandstone reservoirs was enhanced with increasing feldspar content, the pore-throat structure complexity was also stronger, resulting in the reduction seepage capacity of fluid.